PC wear-resistant engineering plastic and preparation method thereof

By using wear resistance additives and dimethyl hydroxy silicone oil in polycarbonate composite materials, the problem of poor wear resistance and flame retardant improvement of polycarbonate composite materials is solved, and the wear resistance of the material is significantly improved and flame retardant properties.

CN119177012AInactive Publication Date: 2024-12-24FOSHAN KAILIANFU HARDWARE CO LTD
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202411226126.0
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-09-03
Publication Date
2024-12-24
Estimated Expiration
Not applicable · inactive patent

AI Technical Summary

Technical Problem

The wear resistance, toughness and flame retardancy of existing polycarbonate composite materials are poorly improved, mainly due to the poor dispersion performance of silicon carbide whiskers.

Method used

Wear-resistant additives are used, containing boron nitride and graphene oxide structures, and their dispersion and compatibility are improved through reactions, and dimethyl hydroxy silicone oil and maleic anhydride grafted ethylene-1-octene copolymer are added to combine Crosslinking agent, prepare PC wear-resistant engineering plastics.

Benefits of technology

The wear resistance, toughness and flame retardancy of polycarbonate engineering plastics are significantly improved, and the wear resistance and combustion performance of the material is enhanced by improving the dispersion and compatibility of the additives.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure BDA0005024606040000101
    Figure BDA0005024606040000101
  • Figure BDA0005024606040000111
    Figure BDA0005024606040000111
Patent Text Reader

Abstract

The invention relates to a PC wear-resistant engineering plastic and a preparation method thereof, and belongs to the technical field of plastics, the PC wear-resistant engineering plastic comprises the following raw materials by weight: 50-60 parts of bisphenol A polycarbonate, 20-30 parts of a wear-resistant auxiliary agent, 8-10 parts of dimethyl hydroxyl silicone oil, 2-3 parts of a maleic anhydride grafted ethylene-1-octylene copolymer and 1-2 parts of a cross-linking agent; according to the PC wear-resistant engineering plastic, the wear-resistant aid and the cross-linking agent are added, the wear-resistant aid and the cross-linking agent cooperate with each other, the toughness and compatibility of the PC wear-resistant engineering plastic are improved, and meanwhile, the wear-resistant aid contains a boron nitride structure and a graphene oxide structure which are high in toughness and good in wear resistance, so that the wear resistance of the PC wear-resistant engineering plastic is improved. The problems of poor self dispersibility and compatibility of the PC wear-resistant engineering plastic are solved by organic combination of the PC and the wear-resistant auxiliary through reaction, the wear resistance and toughness of the PC wear-resistant engineering plastic are further improved, and in addition, sulfonic acid groups contained in the wear-resistant auxiliary and a graphene oxide structure in the wear-resistant auxiliary cooperate with each other, so that the flame retardance of the PC engineering plastic is improved.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention belongs to the technical field of plastics, and in particular relates to PC wear-resistant engineering plastics and a preparation method thereof. Background Art

[0002] Polycarbonate is a high molecular polymer material containing carbonate groups in its molecular chain and is also one of the five general engineering plastics. Polycarbonate is widely used in automobile manufacturing, food packaging, medical equipment, aerospace and other fields due to its excellent properties such as good thermal stability, high mechanical strength, high cold resistance and high impact resistance.

[0003] Chinese patent CN103289341 A discloses a reinforced polycarbonate composite material, comprising the following raw materials in parts by weight: 100-120 parts of polycarbonate, 8-15 parts of carbon fiber, 1-2 parts of silicon carbide whiskers, 1-2 parts of pearlescent powder, 1640.1-0.8 parts of antioxidant, 0.3-1.5 parts of coupling agent, 3-6 parts of ammonium polyphosphate, 2-8 parts of dimethyl trimethylsilylmethylphosphonate and 1-2 parts of maleic anhydride grafted ethylene-1-octene copolymer. The invention not only uses carbon fiber to reinforce polycarbonate, but also uniformly disperses silicon carbide into polycarbonate, greatly enhancing the wear resistance and impact resistance of polycarbonate. At the same time, the product of the invention has good flame retardant properties. However, silicon carbide whiskers have the problem of poor dispersion performance. Simply stirring all the mixtures will not have a good effect on improving the performance of the polycarbonate composite material. Summary of the invention

[0004] The purpose of the present invention is to provide to solve the following technical problems:

[0005] How to improve the wear resistance, toughness and flame retardancy of PC wear-resistant engineering plastics.

[0006] The purpose of the present invention can be achieved through the following technical solutions:

[0007] A PC wear-resistant engineering plastic comprises the following raw materials in parts by weight: 50-60 parts of bisphenol A polycarbonate, 20-30 parts of wear-resistant additive, 8-10 parts of dimethylhydroxy silicone oil, 2-3 parts of maleic anhydride grafted ethylene-1-octene copolymer and 1-2 parts of crosslinking agent;

[0008] The preparation method of the PC wear-resistant engineering plastic comprises the following steps:

[0009] According to weight, bisphenol A polycarbonate, wear-resistant additive, dimethyl hydroxy silicone oil, maleic anhydride grafted ethylene-1-octene copolymer and crosslinking agent are dry-mixed in a high-speed mixer for 7-8 minutes, and then placed in a twin-screw extruder for melt extrusion, cooling, pelletizing, and obtaining PC wear-resistant engineering plastics;

[0010] Among them, the temperature of the twin-screw extruder zone 1 is 120-130°C, zone 2 is 170-180°C, zone 3 is 230-240°C, zone 4 is 240-250°C; zone 5 is 210-220°C, the residence time is 1-2min, and the pressure is 10-15Mpa.

[0011] Furthermore, the preparation method of the wear-resistant additive comprises the following steps:

[0012] Under nitrogen protection, functionalized boron nitride and N,N-dimethylformamide were mixed, heated to 60°C, potassium persulfate was added, stirred and dispersed, graphene oxide enhancer was added, heated to 70°C, the temperature was kept constant, and the reaction was continued with stirring for 3-4 hours. After the reaction was completed, the pH value was adjusted to 7 with sodium hydroxide, filtered, dried, and ground through a 50-mesh sieve to obtain a wear-resistant additive;

[0013] Among them, the dosage ratio of functionalized boron nitride, potassium persulfate, functionalized graphene and N,N-dimethylformamide is 0.1-0.2g:1-1.5mg:0.1-0.2g:50-60mL. Potassium persulfate is used as an initiator, and functionalized boron nitride containing unsaturated double bonds and functionalized graphene containing unsaturated double bonds are copolymerized to obtain a wear-resistant additive.

[0014] Furthermore, the preparation method of functionalized boron nitride comprises the following steps:

[0015] Step A1, add citric acid and 95wt% ethanol aqueous solution into a three-necked flask, raise the temperature to 160-165°C under nitrogen protection, heat and stir until melted, add hexagonal boron nitride, continue stirring for 10-12h, wash with water until neutral, wash, filter and dry to obtain nano boron nitride;

[0016] The dosage ratio of citric acid, 95wt% ethanol aqueous solution and hexagonal boron nitride is 5-6g:50-60mL:1-2g. The hexagonal boron nitride is heat-treated with molten citric acid to break its BN bonds, resulting in a large number of B and N vacancy defects, which are conducive to the formation of -OH and -NH- functional groups at the defects and edges of the nano-boron nitride layer, expanding the distance between the boron nitride layers, and obtaining nano-boron nitride.

[0017] Step A2, adding nano boron nitride, itaconic acid and N,N-dimethylformamide into a three-necked flask, ultrasonically dispersing for 1-2 hours, heating to 60-70°C, stirring for reaction for 10-12 hours, and washing and drying after the reaction to obtain functionalized boron nitride;

[0018] The dosage ratio of nano-boron nitride, itaconic acid and dimethylformamide is 0.1-0.2g: 0.15-0.3g: 30-40mL. The amidation reaction between the amino group on the nano-boron nitride and the carboxyl group on itaconic anhydride further improves the dispersion performance of the nano-boron nitride.

[0019] Furthermore, the preparation method of the graphene oxide enhancer comprises the following steps:

[0020] Step B1, under nitrogen protection, add graphene oxide and deionized water into a three-necked flask, ultrasonically disperse for 1-2 hours, add tris(hydroxymethyl)aminomethane, heat to 70-80°C, heat under reflux and react for 6-8 hours. After the reaction is completed, filter, wash, vacuum dry, and grind into powder to obtain amino graphene oxide;

[0021] The amount ratio of graphene oxide, deionized water and tris(hydroxymethyl)aminomethane is 0.1-0.2 g: 600-700 mL: 1-2 g, and the epoxy groups on the graphene oxide react with tris(hydroxymethyl)aminomethane to undergo nucleophilic substitution reaction to obtain aminated graphene oxide;

[0022] Step B2, under nitrogen protection, add amino graphene and xylene into a three-necked flask, ultrasonically disperse for 1-2 hours, add allyl succinic anhydride, heat to 140-150° C., react for 4-6 hours, and after the reaction is completed, filter and wash, and vacuum dry to obtain functionalized graphene;

[0023] The amount ratio of the amino graphene, xylene and allyl succinic anhydride is 0.1-0.2 g: 100-200 mL: 1.5-2.5 g, and the amino group in the functionalized graphene reacts with the anhydride group on the allyl succinic anhydride to generate the functionalized graphene containing an amide group;

[0024] Step B3, adding functionalized graphene oxide and deionized water into a three-necked flask, ultrasonically dispersing for 1-2 hours, adding KOH to adjust the pH value to 8-9, and then adding aminophenolsulfonic acid, heating to 75-80° C. under nitrogen protection, stirring and reacting for 0.5-1 hour, and after the reaction is completed, washing and drying to obtain a graphene oxide enhancer;

[0025] The mass ratio of functionalized graphene oxide, deionized water and aminophenol sulfonic acid is 0.1-0.2g:500-600mL:1.5-3g; the modification treatment is carried out by using aminophenol sulfonic acid, and the amino groups of aminophenol sulfonic acid and the carboxyl groups on the surface of graphene oxide undergo amidation reaction and are grafted onto the surface of graphene oxide. The reaction can expand the spacing between the amino-modified graphene oxide flakes, reduce the agglomeration of the amino-modified graphene oxide, and improve the dispersion performance of the amino-modified graphene oxide.

[0026] Furthermore, the cross-linking agent is one or more of 4,4-diphenylmethane diisocyanate and isophorone diisocyanate mixed in any ratio.

[0027] Beneficial effects of the present invention:

[0028] (1) In order to improve the wear resistance and flame retardancy of polycarbonate engineering plastics, a wear-resistant additive is added in the present invention. The wear-resistant additive contains a boron nitride structure and a graphene oxide structure. The boron nitride and graphene oxide structures themselves have good toughness and wear resistance. The two structures are organically combined through reaction to improve their own poor dispersibility and compatibility, and the wear resistance and toughness of PC wear-resistant engineering plastics are further improved. At the same time, the sulfonic acid group contained in the wear-resistant additive can promote CO during combustion. 2 and H 2 The release of O, through this effect, cooperates with the graphene oxide structure in the wear-resistant additive to promote the formation of interconnected carbon layers during combustion, further improving the flame retardancy of polycarbonate engineering plastics.

[0029] (2) Dimethylhydroxysilicone oil is added in the present invention. The dimethylhydroxysilicone oil with low surface energy has good lubrication effect. At the same time, the wear-resistant additive contains carboxyl and carboxyl groups. The carboxyl and carboxyl groups can produce hydrogen bonds with the amino groups in the dimethylhydroxysilicone oil, further enhancing the dispersibility and compatibility of the wear-resistant additive. By enhancing the dispersibility of the wear-resistant additive in polycarbonate engineering plastics, the wear resistance of polycarbonate engineering plastics is further improved.

[0030] (3) The present invention adds maleic anhydride grafted ethylene-1-octene copolymer and a crosslinking agent. The maleic anhydride grafted ethylene-1-octene copolymer not only has good toughness itself but also has good compatibility with polycarbonate as a thermoplastic elastomer, and can significantly enhance the toughness of polycarbonate engineering plastics. At the same time, the hydroxyl groups on the surfaces of boron nitride and graphene oxide in the wear-resistant additive can chemically crosslink with -NCO in the crosslinking agent to form a carbamate bond, so that the prepared PC wear-resistant engineering plastics can further improve its toughness while maintaining its elasticity. DETAILED DESCRIPTION

[0031] The following will be combined with the embodiments of the present invention to clearly and completely describe the technical solutions in the embodiments of the present invention. Obviously, the described embodiments are only part of the embodiments of the present invention, not all of the embodiments. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without creative work are within the scope of protection of the present invention.

[0032] Example 1

[0033] This embodiment provides a method for preparing functionalized boron nitride, comprising the following steps:

[0034] Step A1, add 5g of citric acid and 50mL of 95wt% ethanol aqueous solution into a three-necked flask, heat to 160°C under nitrogen protection, heat and stir until melted, add 1g of hexagonal boron nitride, continue stirring for 10h, wash with water until neutral, wash, filter and dry to obtain nano boron nitride;

[0035] Step A2, add 0.1g of nano boron nitride, 0.15g of itaconic acid and 30mL of N,N-dimethylformamide into a three-necked flask, ultrasonically disperse for 1h, heat to 60°C, stir and react for 10h, and after the reaction is completed, wash and dry to obtain functionalized boron nitride.

[0036] Example 2

[0037] This embodiment provides a method for preparing functionalized boron nitride, comprising the following steps:

[0038] Step A1, add 6g of citric acid and 60mL of 95wt% ethanol aqueous solution into a three-necked flask, under nitrogen protection, heat to 165°C, heat and stir until melted, add 2g of hexagonal boron nitride, continue stirring for 12h, wash with water until neutral, wash, filter and dry to obtain nano boron nitride;

[0039] Step A2, add 0.2g of nano boron nitride, 0.3g of itaconic acid and 40mL of N,N-dimethylformamide into a three-necked flask, ultrasonically disperse for 2h, heat to 70°C, stir and react for 12h, and after the reaction is completed, wash and dry to obtain functionalized boron nitride.

[0040] Example 3

[0041] This embodiment provides a method for preparing a graphene oxide reinforcing agent, comprising the following steps:

[0042] Step B1, under nitrogen protection, add 0.1 g of graphene oxide and 600 mL of deionized water into a three-necked flask, ultrasonically disperse for 1 h, add 1 g of tris(hydroxymethyl)aminomethane, heat to 70° C., heat under reflux and react for 6 h. After the reaction is completed, filter, wash, vacuum dry, and grind into powder to obtain amino graphene oxide;

[0043] Step B2, under nitrogen protection, add 0.1 g of amino graphene and 100 mL of xylene into a three-necked flask, ultrasonically disperse for 1 h, add 1.5 g of allyl succinic anhydride, heat to 140° C., react for 4 h, and after the reaction is completed, filter and wash, and vacuum dry to obtain functionalized graphene;

[0044] Step B3, add 0.1g functionalized graphene oxide and 500mL deionized water into a three-necked flask, ultrasonically disperse for 1h, add KOH to adjust the pH value to 8, then add 1.5g aminophenolsulfonic acid, raise the temperature to 75°C under nitrogen protection, stir and react for 0.5h, after the reaction is completed, wash and dry to obtain the graphene oxide enhancer.

[0045] Example 4

[0046] This embodiment provides a method for preparing a graphene oxide reinforcing agent, comprising the following steps:

[0047] Step B1, under nitrogen protection, add 0.2 g of graphene oxide and 700 mL of deionized water into a three-necked flask, ultrasonically disperse for 2 h, add 2 g of tris(hydroxymethyl)aminomethane, heat to 80° C., heat under reflux and react for 8 h. After the reaction is completed, filter, wash, vacuum dry, and grind into powder to obtain amino graphene oxide;

[0048] Step B2, under nitrogen protection, add 0.2 g of amino graphene and 200 mL of xylene into a three-necked flask, ultrasonically disperse for 2 h, add 2.5 g of allyl succinic anhydride, heat to 150 ° C, react for 6 h, and after the reaction is completed, filter and wash, and vacuum dry to obtain functionalized graphene;

[0049] Step B3, add 0.2g functionalized graphene oxide and 600mL deionized water into a three-necked flask, ultrasonically disperse for 2h, add KOH to adjust the pH value to 9, then add 3g aminophenolsulfonic acid, heat to 80°C under nitrogen protection, stir and react for 1h, after the reaction is completed, wash and dry to obtain the graphene oxide enhancer.

[0050] Example 5

[0051] This embodiment provides a method for preparing a wear-resistant additive, comprising the following steps:

[0052] Under nitrogen protection, 0.1 g of the functionalized boron nitride prepared in Comparative Example 1 and 50 mL of N,N-dimethylformamide were mixed, the temperature was raised to 60 ° C, 1 mg of potassium persulfate was added, and the mixture was dispersed by stirring. 0.1 g of the graphene oxide enhancer prepared in Comparative Example 2 was added, the temperature was raised to 70 ° C, the temperature was kept constant, and the reaction was continued with stirring for 3 hours. After the reaction was completed, the pH value was adjusted to 7 with sodium hydroxide, and the mixture was filtered, dried, and ground through a 50-mesh sieve to obtain a wear-resistant additive.

[0053] Example 6

[0054] This embodiment provides a method for preparing a wear-resistant additive, comprising the following steps:

[0055] Under nitrogen protection, 0.2 g of the functionalized boron nitride prepared in Comparative Example 3 and 60 mL of N,N-dimethylformamide were mixed, the temperature was raised to 60 ° C, 1.5 mg of potassium persulfate was added, and the mixture was dispersed by stirring. 0.2 g of the graphene oxide enhancer prepared in Comparative Example 4 was added, the temperature was raised to 70 ° C, the temperature was kept constant, and the reaction was continued with stirring for 4 hours. After the reaction was completed, the pH value was adjusted to 7 with sodium hydroxide, and the mixture was filtered, dried, and ground through a 50-mesh sieve to obtain a wear-resistant additive.

[0056] Example 7

[0057] This embodiment provides a PC wear-resistant engineering plastic, comprising the following raw materials in parts by weight: 50 parts of bisphenol A polycarbonate, 20 parts of the wear-resistant additive prepared in Example 5, 8 parts of dimethyl hydroxy silicone oil, 2 parts of maleic anhydride grafted ethylene-1-octene copolymer and 1 part of 4,4-diphenylmethane diisocyanate;

[0058] The preparation method of the PC wear-resistant engineering plastic comprises the following steps:

[0059] According to weight, the above-mentioned various raw materials are dry-mixed in a high-speed mixer for 7 minutes, and then placed in a twin-screw extruder for melt extrusion, cooling, and pelletizing to obtain PC wear-resistant engineering plastics, wherein the temperature of the first zone of the twin-screw extruder is 120°C, the second zone is 170°C, the third zone is 230°C, the fourth zone is 240°C; the fifth zone is 210°C, the residence time is 1 minute, and the pressure is 10Mpa.

[0060] Example 8

[0061] This embodiment provides a PC wear-resistant engineering plastic, comprising the following raw materials in parts by weight: 60 parts of bisphenol A polycarbonate, 30 parts of the wear-resistant additive prepared in Example 6, 10 parts of dimethyl hydroxy silicone oil, 3 parts of maleic anhydride grafted ethylene-1-octene copolymer and 2 parts of isophorone diisocyanate;

[0062] The preparation method of the PC wear-resistant engineering plastic comprises the following steps:

[0063] The above raw materials were dry-mixed in a high-speed mixer for 8 minutes according to weight, and then placed in a twin-screw extruder for melt extrusion, cooling, and pelletizing to obtain PC wear-resistant engineering plastics;

[0064] Among them, the temperature of the twin-screw extruder zone 1 is 130°C, zone 2 is 180°C, zone 3 is 240°C, zone 4 is 250°C; zone 5 is 220°C, the residence time is 2 minutes, and the pressure is 15Mpa.

[0065] Comparative Example 1

[0066] This comparative example is the hexagonal boron nitride in Example 1.

[0067] Comparative Example 2

[0068] The nano boron nitride in Example 1 was replaced by the substance in Comparative Example 1, and the other raw materials and preparation process remained unchanged.

[0069] Comparative Example 3

[0070] The itaconic acid in Example 2 was removed, and the other raw materials and preparation process remained unchanged.

[0071] Comparative Example 4

[0072] The tris(hydroxymethyl)aminomethane in Example 3 was removed, and the other raw materials and preparation process remained unchanged.

[0073] Comparative Example 5

[0074] The allyl succinic anhydride in Example 3 was removed, and the other raw materials and preparation process remained unchanged.

[0075] Comparative Example 6

[0076] The aminophenolsulfonic acid in Example 4 was removed, and the other raw materials and preparation process remained unchanged.

[0077] Comparative Example 7

[0078] The functionalized boron nitride in Example 5 was replaced by the substance in Comparative Example 2, and the other raw materials and preparation process remained unchanged.

[0079] Comparative Example 8

[0080] The functionalized boron nitride in Example 5 was replaced by the substance in Comparative Example 3, and the other raw materials and preparation process remained unchanged.

[0081] Comparative Example 9

[0082] The graphene reinforcing agent in Example 6 was replaced by the substance in Comparative Example 4, and the other raw materials and preparation process remained unchanged.

[0083] Comparative Example 10

[0084] The graphene enhancer in Example 6 was replaced by the substance in Comparative Example 5, and the other raw materials and preparation process remained unchanged.

[0085] Comparative Example 11

[0086] The graphene enhancer in Example 6 was replaced by the substance in Comparative Example 6, and the other raw materials and preparation process remained unchanged.

[0087] Comparative Example 12

[0088] The wear-resistant additive in Example 7 was replaced by the substance in Comparative Example 7, and the other raw materials and preparation process remained unchanged.

[0089] Comparative Example 13

[0090] The wear-resistant additive in Example 7 was replaced by the substance in Comparative Example 8, and the other raw materials and preparation process remained unchanged.

[0091] Comparative Example 14

[0092] The wear-resistant additive in Example 7 was replaced by the substance in Comparative Example 9, and the other raw materials and preparation process remained unchanged.

[0093] Comparative Example 15

[0094] The wear-resistant additive in Example 8 was replaced by the substance in Comparative Example 10, and the other raw materials and preparation process remained unchanged.

[0095] Comparative Example 16

[0096] The wear-resistant additive in Example 8 was replaced by the substance in Comparative Example 11, and the other raw materials and preparation process remained unchanged.

[0097] Comparative Example 17

[0098] The wear-resistant additive in Example 8 was replaced by the substance in Comparative Example 12, and the other raw materials and preparation process remained unchanged.

[0099] Performance Testing

[0100] (I) Sample preparation: Referring to GB / T 35513.2-2017 standard, the PC wear-resistant engineering plastics prepared in Examples 7-8 and Comparative Examples 3-5 were further processed to prepare test samples;

[0101] (II) Performance test: For wear resistance, 0000# steel wool (load 1 kg) was used to rub the sample back and forth 2000 times and then observe the surface condition; according to GB / T 35513.2-2017 standard, and referring to GB / T1040-2006 and GB / T 9341-2000, the tensile strength, elongation at break, flexural strength and flexural modulus of PC wear-resistant engineering plastics were tested respectively; for flame retardant grade (UL94) test, 5 specimens were prepared for each test, the test standard was ASTMD3801-2010, and the specification of the test sample was 127mm×12.7mm×2.7mm. The test results are shown in Table 1:

[0102] Table 1

[0103]

[0104]

[0105] Note: ◎: less than 10 scratches with a length of 1 cm; ○: less than 30 scratches with a length of 1 cm; ×: the surface is completely scratched.

[0106] It can be seen from Table 1 that, compared with Comparative Examples 13-17, the PC wear-resistant engineering plastics prepared in Examples 7-8 have excellent wear resistance, toughness and flame retardancy.

[0107] In the description of the specification, the description with reference to the terms "one embodiment", "example", "specific example", etc. means that the specific features, structures, materials or characteristics described in conjunction with the embodiment or example are included in at least one embodiment or example of the present invention. In this specification, the schematic representation of the above terms does not necessarily refer to the same embodiment or example. Moreover, the specific features, structures, materials or characteristics described can be combined in any one or more embodiments or examples in a suitable manner.

[0108] The above contents are merely examples and explanations of the present invention. Those skilled in the art may make various modifications or additions to the specific embodiments described or replace them in a similar manner. As long as they do not deviate from the invention or exceed the scope defined by the claims, they shall all fall within the protection scope of the present invention.

Claims

1. A PC wear-resistant engineering plastic, characterized in that: The method comprises the following raw materials in parts by weight: 50-60 parts of bisphenol A polycarbonate, 20-30 parts of wear-resistant additive, 8-10 parts of dimethyl hydroxy silicone oil, 2-3 parts of maleic anhydride grafted ethylene-1-octene copolymer and 1-2 parts of crosslinking agent; The preparation method of the wear-resistant additive comprises the following steps: Under nitrogen protection, functionalized boron nitride and N,N-dimethylformamide were mixed, heated to 60°C, potassium persulfate was added, stirred and dispersed, functionalized graphene was added, heated to 70°C, the temperature was kept constant, and the reaction was continued with stirring for 3-4 hours. After the reaction, the pH value was adjusted to 7 with sodium hydroxide, filtered, dried, and ground through a 50-mesh sieve to obtain a wear-resistant additive.

2. A PC wear-resistant engineering plastic according to claim 1, characterized in that: The dosage ratio of functionalized boron nitride, potassium persulfate, functionalized graphene and N,N-dimethylformamide is 0.1-0.2g: 1-1.5mg: 0.1-0.2g: 50-60mL.

3. A PC wear-resistant engineering plastic according to claim 1, characterized in that: The preparation method of functionalized boron nitride comprises the following steps: Step A1, add citric acid and 95wt% ethanol aqueous solution into a three-necked flask, raise the temperature to 160-165°C under nitrogen protection, heat and stir until melted, add hexagonal boron nitride, continue stirring for 10-12h, wash with water until neutral, wash, filter and dry to obtain nano boron nitride; Step A2, add nano boron nitride, itaconic acid and N,N-dimethylformamide into a three-necked flask, ultrasonically disperse for 1-2 hours, heat to 60-70°C, stir and react for 10-12 hours, and after the reaction is completed, wash and dry to obtain functionalized boron nitride.

4. A PC wear-resistant engineering plastic according to claim 3, characterized in that: In step A1, the usage ratio of citric acid, 95wt% ethanol aqueous solution and hexagonal boron nitride is 5-6g:50-60mL:1-2g.

5. A PC wear-resistant engineering plastic according to claim 3, characterized in that: In step A2, the dosage ratio of nano boron nitride, itaconic acid and N,N-dimethylformamide is 0.1-0.2 g: 0.15-0.3 g: 30-40 mL.

6. A PC wear-resistant engineering plastic according to claim 1, characterized in that: The preparation method of the graphene oxide reinforcing agent comprises the following steps: Step B1, under nitrogen protection, add graphene oxide and deionized water into a three-necked flask, ultrasonically disperse for 1-2 hours, add tris(hydroxymethyl)aminomethane, heat to 70-80°C, heat under reflux and react for 6-8 hours. After the reaction is completed, filter, wash, vacuum dry, and grind into powder to obtain amino graphene oxide; Step B2, under nitrogen protection, add amino graphene and xylene into a three-necked flask, ultrasonically disperse for 1-2 hours, add allyl succinic anhydride, heat to 140-150° C., react for 4-6 hours, and after the reaction is completed, filter and wash, and vacuum dry to obtain functionalized graphene; Step B3, add functionalized graphene oxide and deionized water into a three-necked flask, ultrasonically disperse for 1-2 hours, add KOH to adjust the pH value to 8-9, then add aminophenolsulfonic acid, heat to 75-80° C. under nitrogen protection, stir and react for 0.5-1 hour, and after the reaction is completed, wash and dry to obtain the graphene oxide enhancer.

7. A PC wear-resistant engineering plastic according to claim 6, characterized in that: In step B1, the usage ratio of graphene oxide, deionized water and tris(hydroxymethyl)aminomethane is 0.1-0.2 g:600-700 mL:1-2 g.

8. The PC wear-resistant engineering plastic according to claim 6, characterized in that: In step B2, the usage ratio of amination graphene, xylene and allyl succinic anhydride is 0.1-0.2 g:100-200 mL:1.5-2.5 g.

9. The PC wear-resistant engineering plastic according to claim 6, characterized in that: In step B3, the mass ratio of functionalized graphene oxide, deionized water and aminophenolsulfonic acid is 0.1-0.2 g: 500-600 mL: 1.5-3 g.

10. A method for preparing the PC wear-resistant engineering plastic according to any one of claims 1 to 9, characterized in that: The following steps are involved: According to weight, bisphenol A polycarbonate, wear-resistant additive, dimethyl hydroxy silicone oil, maleic anhydride grafted ethylene-1-octene copolymer and crosslinking agent are dry-mixed in a high-speed mixer for 7-8 minutes, and then placed in a twin-screw extruder for melt extrusion, cooling, pelletizing, and obtaining PC wear-resistant engineering plastics.